Sp1‐mediated ectopic expression of T‐cell lymphoma invasion and metastasis 2 in hepatocellular carcinoma. (14th January 2016) - Yen, Wei‐Hsuan; Ke, Wu‐Sian; Hung, Jan‐Jong; Chen, Tsung‐Ming; Chen, Jia‐Shing; Sun, H. S.
Abstract: T‐cell lymphoma invasion and metastasis 2 ( TIAM2 ) is a neuron‐specific protein that has been found ectopically expressed in hepatocellular carcinoma (HCC). Results from clinical specimens and cellular and animal models have shown that the short form of TIAM2 ( TIAM2S ) functions as an oncogene in the tumorigenesis of liver cancer. However, the regulation of TIAM2S ectopic expression in HCC cells remains largely unknown. This study aimed to identify the mechanism underlying the ectopic expression of TIAM2S in liver cancer cells. In this report, we provide evidence illustrating that Sp1 binds directly to the GC box located in the TIAM2S core promoter. We further demonstrated that overexpression of Sp1 in HepaRG cells promotes endogenous TIAM2S mRNA and protein expressions, and knockdown of Sp1 in 2 HCC cell lines, HepG2 and PLC/PRF/5, led to a substantial reduction in TIAM2S mRNA and protein in these cells. Of 60 paired HCC samples, 70% showed a significant increase (from 1.1‐ to 3.6‐fold) in Sp1 protein expression in the tumor cells. The elevated Sp1 expression was highly correlated with both TIAM2S mRNA and protein expressions in these samples. Together, these results illustrate that Sp1 positively controls TIAM2S transcription and that Sp1‐mediated transcriptional activation is essential for TIAM2S ectopic expression in liver cancer cells. Abstract : Previously, our study demonstrated that aberrant expression of the short form of TIAM2 (TIAM2S) underlies TIAM2‐mediated tumorigenesis. However, the regulation of TIAM2S ectopic expression in the cancer cells remains unknown. In this report, we defined TIAM2S core promoter region and showed that specific protein 1 (Sp1) binds directly to the GC box located in the TIAM2S core promoter to activate TIAM2S mRNA expression. We further demonstrated that Sp1 protein expression was upregulated in the HCC samples and the elevated Sp1 level was highly correlated with both TIAM2S mRNA and protein expressions in these samples. Collectively, these data demonstrate that Sp1 positively controls TIAM2S transcription and that Sp1‐mediated transcriptional activation is essential for TIAM2S ectopic expression in liver cancer cells.